Pengaruh Harga terhadap Keputusan Pembelian Perhiasan di Toko Emas Amir Syah Kecamatan Panyabungan - Rini Wahyuni; Vebri Sugiharto; Mufti Fahrizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of price on jewelry purchasing decisions at the Amir Syah gold shop, using price as an independent variable and purchasing decisions as the dependent variable. The population used in the research were consumers who made purchases at the Amir Syah gold shop in 2023 and the sample was 84 respondents. The type of research used is quantitative, data collection techniques are observation, documentation and questionnaires. The analysis method for this research uses validity tests, reliability tests, normality tests, heteroscedasticity tests, simple linear regression tests and hypothesis tests. All of these tests were carried out using the SPSS version 25 program. Based on the results of the t test, tcount = 6.579 ttable > 1.664 and the sig value = 0.000 at a significance level of 0.05. So it can be concluded that the hypothesis is accepted, which means that there is a positive and significant influence of price on purchasing decisions because the results of the t test fulfill all of the first conditions, namely tcount > ttable (6.579 > 1.664) and the sig number <005 (0.000<0.05). Based on the coefficient of determination (R2) value of 0.345 or 34.5%. This means that the ups and downs in decisions to purchase jewelry at the Amir Syah gold shop in Panyabungan District due to the influence of prices can be anticipated. Through this regression equation, the remaining 65.5% is influenced by other factors or variables outside this research.